How can gender research trigger changes to influence breeding priorities - Polar, Vivian; Ashby, Jacqueline A.; Tufan, Hale Ann (International Potato Center, 2023)
Significant progress in agricultural technology development have remained persistently blind to social and gender inequalities. Creating agricultural research ecosystems and institutions that address gender inequality require structural and systemic analysis. One of the major areas of investment in agricultural innovation is plant breeding. Integrating social welfare objectives in plant breeding is a good starting point to catalyze progress toward genderequality objectives in research for development at a global scale, yet if devoid of structural change these efforts risk falling short of expectations. Intentionally addressing gender can reshape the technical options, goals and intended impact of plant-breeding programs. Improving the benefits delivered to rural women through plant breeding can be achieved through new methods and learning, critically analyzing systematic barriers to equitable plant-breeding research, and documenting case studies that demonstrate positive change. This paper analyzes different cases and experiences of gender-intentional breeding across crops, geographies and institutional frameworks to explore: (a) how are gender-responsive and other social-inclusion objectives implemented in breeding programs and why? (b) what methods, tools and instruments can successfully help this process? and (c) what type of strategies can be used to integrate multidisciplinary work into defining new breeding objectives? This analysis generated a comprehensive overview of factors that influence how, when and why results from gender research can trigger changes in breeding priorities, processes or decisions, and how to better design structural innovations across different regional and institutional contexts to enhance technology design.